DATA-driven shock impact of COVID-19 on the market financial system. Issue 1 (January 2022) - Li, Shaoling; Yan, Yuwei
Highlights: We built a data model processing system to analyzes the shock effect from three aspects. Our work uses analyzes model data and outputs the results and compares them with the actual situation. The proposed research method has significant effects and has certain reference value for studying the shock effect of the epidemic on the financial system. Abstract: The Corona Virus Disease 2019(COVID-19) has a dramatic effect on my country's market and financial system. Although China has controlled the deterioration of the epidemic, this global epidemic will inevitably have an impact on the global economy including China. In order to study the shock effect of the COVID-19 on the market financial system, this paper builds a data model processing system based on the event analysis method, and analyzes the shock effect from three aspects of supply chain finance, financial securities, and corporate financial systems. Moreover, this paper uses crawler technology to obtain valid data from major websites, analyzes model data with mathematical statistics combined with event models, and outputs the results and compares them with the actual situation. Through data analysis, it can be seen that the model constructed in this paper can effectively reflect the shock effect of the COVID-19 on the market financial system. Finally, the comparison method is used to compare the research results with the actual situation. The results show that the two are basically the same. Therefore, it can be seen that the proposed research method has significant effects and has certain reference value for studying the shock effect of the epidemic on the financial system.